C-581/20, TOTO: a missed opportunity to cast light on Article 35 of the Brussels I bis Regulation? - Santaló Goris, Carlos (CUADERNOS DE DERECHO TRANSNACIONAL, 2022)
In C-581/20, TOTO, the CJEU was asked about two key aspects of the Brussels I bis Regulation jurisdictional regime for interim proceedings. One is whether it is possible to apply for the same provisional measure before the courts of two Member States. The other is whether access to interim measures throughout Article 35 is subject to a European autonomous regime of prerequisites. To the first point, and against the Advocate General Opinion, the CJEU replies that such practice is allowed. Concerning the second point, the CJEU does not even clarify whether there is an autonomous regime of prerequisites exists or not. The CJEU’s answers are less ambitious than the expectations generated by the preliminary reference. This paper offers a comprehensive analysis of the judgment TOTO, evaluating its impact on the interpretation of the Brussels I bis Regulation.
Keywords: Brussels I bis Regulation; civil and commercial matters; enforcement; provisional measures; interim measures; choice of court agreements; lis pendens; irreconciliable judgments